Teaching "Global Project Management" with Distributed Team Projects - WEINBERG, Randy (Institutional Knowledge at Singapore Management University, 2007)
The education of rising professionals must keep pace with changing forces of globalization and the realities of distributed work. Students who understand the basics of global project management, teamwork and collaboration are likely to find themselves at a competitive advantage over those who do not. This article describes the experiences in an undergraduate course called Global Project Management offered concurrently at two universities, one in the U.S. and one in Singapore, and incorporating collaborative student projects.